2015
DOI: 10.1016/j.cct.2015.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment strategies in two reproductive medicine network infertility trials

Abstract: Background Recruitment of individuals into clinical trials is a critical step in completing studies. Reports examining the effectiveness of different recruitment strategies, and specifically in infertile couples, are limited. Methods We investigated recruitment methods used in two NIH sponsored trials, Pregnancy in Polycystic Ovary Syndrome (PPCOS II) and Assessment of Multiple Intrauterine Gestations from Ovarian Stimulation (AMIGOS), and examined which strategies yielded the greatest number of participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
3
6
0
Order By: Relevance
“…Across the two RCTs, recruitment proved to be more resource intensive and had a higher proportion of screen failures than initially anticipated during trial design and planning, requiring an extension to the recruitment period and the addition of sites. These recruitment struggles are similar to those reported for other disciplines too (Lloyd, Dean, and Ada 2010;Usadi et al 2015).…”
Section: Recruitment Methods: Limitationssupporting
confidence: 86%
See 3 more Smart Citations
“…Across the two RCTs, recruitment proved to be more resource intensive and had a higher proportion of screen failures than initially anticipated during trial design and planning, requiring an extension to the recruitment period and the addition of sites. These recruitment struggles are similar to those reported for other disciplines too (Lloyd, Dean, and Ada 2010;Usadi et al 2015).…”
Section: Recruitment Methods: Limitationssupporting
confidence: 86%
“…Like others (e.g. Usadi et al 2015), professional referrals to CLARITY-1 were found to be most effective when there was an existing close relationship between specialties and the trial team. Similarly, Lloyd, Dean, and Ada (2010) also commented that referral strategies are more successful and efficient than advertising strategies at recruiting community-dwelling stroke survivors.…”
Section: Recruitment Methods: Limitationsmentioning
confidence: 55%
See 2 more Smart Citations
“…This implies that recruitment may be more successful if participants hear about studies from trusted individuals, such as their physicians or pharmacists [2, 27], and it might explain why health care providers enrolled the most participants in our study. Similarly, personal referrals have been shown to be quite successful at persuading people to enroll [2, 11–13, 26, 28, 32, 33]; which we also noted with the success of the ”word of mouth” strategy. Mail-based recruitment strategies can be challenging to implement.…”
Section: Discussionsupporting
confidence: 70%